1999
DOI: 10.1007/s00585-999-0855-1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical observations of the MLT, latitude and size of pulsed ionospheric flows with the CUTLASS Finland radar

Abstract: Abstract. A study has been performed on the occurrence of pulsed ionospheric¯ows as detected by the CUTLASS Finland HF radar. These¯ows have been suggested as being created at the ionospheric footprint of newly-reconnected ®eld lines, during episodes of magnetic¯ux transfer into the terrestrial magnetosphere (¯ux transfer events or FTEs). Two years of both hightime resolution and normal scan data from the CUT-LASS Finland radar have been analysed in order to perform a statistical study of the extent and locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 41 publications
5
29
1
Order By: Relevance
“…Ridley et al, 1998). Our findings also support Lockwood (1997) and Provan and Yeoman (1999), who considered cusp particle precipitation observations and plasma flow data and concluded that the ionospheric projection of the magnetopause X-line was wider than that predicted solely by cusp particle precipitation data (Newell and Meng, 1992).…”
Section: The Longitudinal Extent Of the Magnetopause Reconnection X-linesupporting
confidence: 87%
“…Ridley et al, 1998). Our findings also support Lockwood (1997) and Provan and Yeoman (1999), who considered cusp particle precipitation observations and plasma flow data and concluded that the ionospheric projection of the magnetopause X-line was wider than that predicted solely by cusp particle precipitation data (Newell and Meng, 1992).…”
Section: The Longitudinal Extent Of the Magnetopause Reconnection X-linesupporting
confidence: 87%
“…While the range of MLT included in this survey is very large, extending well away from noon, 75% of time series are taken between 0800 and 1600 MLT with a peak around 1000 MLT. Our range of MLT is larger than that of Provan and Yeoman [1999] who observed PIFs from 0250 to 1650 MLT with the CUTLASS Finland radar (also with a peak around 1000 MLT). This is probably due to our inclusion of all suitable time series within the radar field of view at the time of PIFs.…”
Section: Methodscontrasting
confidence: 67%
“…However, it is important here to attempt to clarify the nomenclature that has been used in previous publications for dayside transients observed by HF radars, and to justify the terminology adopted in this paper. As noted in the Introduction, three terms to describe such features are in current usage: flow channel events (FECs) (Pinnock et al, 1993Neudegg et al, 1999Neudegg et al, , 2000, pulsed ionospheric flows (PIFs) (Provan et al, 1998;Provan and Yeoman, 1999;McWilliams et al, 2000) and polewardmoving radar auroral forms (PMRAFs) (Wild et al, 2001). FCEs and PIFs, as their names suggest, describe bursts of enhanced flow in a background of slower-moving plasma.…”
Section: Cutlass Hf Observationsmentioning
confidence: 99%
“…These include many observations by the HF coherent scatter radars of the Super Dual Auroral Radar Network (SuperDARN) of dayside transients, which generally exhibit an antisunward motion. Dependant on their exact characteristics, and crucially, the parameter in which they are identified, these ionospheric transients have been termed flow channel events (FCEs) (Pinnock et al, 1993;1995;Neudegg et al, 1999;, pulsed ionospheric flows (PIFs) (Provan et al, 1998;Provan and Yeoman, 1999;McWilliams et al, 2000) or poleward-moving radar auroral forms (PMRAFs) (Wild et al, 2001). However, it has become increasingly evident that these three so-called forms of dayside transients are in fact very much related, and in some cases actually describe the same phenomena; this is discussed by Wild et al (2001) and in more detail later in the present paper.…”
Section: Introductionmentioning
confidence: 99%